Assessment of Serum Total Cholesterol and Triglycerides in Bipolar Disorder Subjects - Tehmina Tariq, Sana Sarmad, Muhammad Adnan Sadiq, Shama Akram, Sumera Saghir, Fahimul-Haq, Samiah Shahid, Javed Anver Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bipolar disorder (BD), being a psychiatric condition, is defined as mood swing that alternates between mania, hypomania, and depression. Studies have been conducted globally to assess lipid profile for bipolar disorder with varying results. No such studies have been conducted in Pakistan. Therefore, present study was designed to assess total cholesterol and triglycerides in clinically diagnosed bipolar disorder. Materials and methods: One hundred and twelve blood samples were collected of diagnosed bipolar patients visiting Sheikh Zayd Hospital (SZH) and Punjab Institute of Mental Health (PIMH) Lahore. Total Cholesterol (TC) and Triglycerides (TG), were estimated using standard biochemical methods Results: Results obtained were statistically analyzed using SPSS. A total of 112 bipolar patients, 48 (58.5%) were manic, 26 (31.7%) were depressive, 8 (9.8%) were euthymic. The mean Cholesterol level (191.01±40.67 mg/dl),in bipolar group ( manic, depressive and euthymic) were statistically significant as compared to control group with p-value 0.026. The mean TG level (163.01±89.08 mg/dl), in bipolar and control groups were statistically insignificant with p-value 0.609. Conclusions: The present study suggests that TC level is raised in depressive patients. TG levels were same in bipolar and control groups. Keywords: Bipolar Disorder, Lipid Profile, Total Cholesterol, Triglyceride.